2018
DOI: 10.1002/hyp.13260
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the water holding capacity of the critical zone using near‐surface geophysics

Abstract: In high-mountain watersheds, the critical zone holds crucial life-sustaining water stores in the form of shallow groundwater aquifers. To better understand the role that the critical zone plays in moderating hydrologic response to fluxes at the surface and in the subsurface, the hydrologic properties must be characterized over large scales (i.e., that of the watershed). In this study, we estimate porosity from geophysical measurements across a 58-ha area to depths of~80 m. Our observations include velocities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 103 publications
(139 reference statements)
7
89
0
2
Order By: Relevance
“…We interpret the region between ∼14 and 17 m as saturated saprolite instead of a large fracture zone for three reasons. First, the maximum water content measured by the borehole NMR (0.34 m 3 m −3 ) is consistent with the average measured porosity of saprolite (0.34 ± 0.06 m 3 /m 3 ) based on 25 measurements collected along the ridge in the study area (Flinchum et al, 2018a, 2018b). Second, it occurs just above the casing depth (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We interpret the region between ∼14 and 17 m as saturated saprolite instead of a large fracture zone for three reasons. First, the maximum water content measured by the borehole NMR (0.34 m 3 m −3 ) is consistent with the average measured porosity of saprolite (0.34 ± 0.06 m 3 /m 3 ) based on 25 measurements collected along the ridge in the study area (Flinchum et al, 2018a, 2018b). Second, it occurs just above the casing depth (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…8c). The water table measured by hand and reported by Flinchum et al (2018a) is associated with increased water content observed in six of the seven soundings (Fig. 8c).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…New methodological advances, particularly using geophysical methods (such as seismic refraction and nuclear magnetic resonance) can be used to test these models and characterise the resulting subsurface porosity structure that determines the water‐holding capacity of weathered bedrock (e.g. Flinchum et al , ; Rempe et al ., ).…”
Section: Water Resources In Weathered Bedrock Determine Plant Distribmentioning
confidence: 99%